METAFORA PADA LAGU BERTEMAKAN MUSIM PANAS KARYA MAFUMAFU - Sri Muryati; Bekti Setio Astuti; Trismanto Trismanto (Universitas Diponegoro, 2025)
This study investigates the types and meanings of metaphors found in summer-themed songs by the Japanese musician Mafumafu. The use of metaphor in song lyrics serves to enhance aesthetic value without diminishing the intended message. This research employs a descriptive qualitative method. The classification of metaphors is based on the theory of Stephen Ullman (2007), while the metaphor analysis refers to the framework proposed by Knowles and Moon (2006). The data were collected from six summer-themed songs by Mafumafu using observation and note-taking techniques, and analyzed using the Immediate Constituent Analysis (BUL) technique. The results reveal a total of 29 metaphorical expressions in the lyrics. Among these, abstraction metaphors are the most frequently used, totaling 15 instances. These are followed by anthropomorphic metaphors (6 instances), synesthetic metaphors (5 instances), and animal metaphors (3 instances). The findings indicate that Mafumafu tends to use abstraction metaphors dominantly, suggesting a stylistic preference for expressing complex emotions and imagery in a poetic and imaginative way. These metaphors contribute significantly to the linguistic beauty and depth of the song lyrics. <a href=